The Influence of Transformational Leadership and Affective Commitment on Employee Creativity at Juwata Tarakan Airport Through Work Motivation as A Mediating Variable - Fahrudin Rahmad; Kabul Wahyu Utomo; Ana Sriekaningsih (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose : The purpose of this research is to analyze of The Influence Of Transformational Leadership And Affective Commitment On Employee Creativity At Juwata Tarakan Airport Through Work Motivation As A Mediating Variable Design/methodology/approach : This research was conducted to analyze whether is an influence between independence and dependent variable. The study population was employees in the manufacturing industry At Juwata Tarakan Airport. which is a government organization under the Directorate General of Civil Aviation, Ministry of Transportation Findings : The research results show that The Influence Of Transformational Leadership And Affective Commitment On Employee Creativity At Juwata Tarakan Airport Through Work Motivation As A Mediating Variable Research limitation/implication : This research was conducted at only one Juwata Tarakan Airport. Future research is expected to expand the intervening variables and expand the sample size. Paper type : Research paper Keywords: Transformational leadership, affective commitment, work motivation, employee creativity